From coblabberation to collaboration: an interview study of professional learning communities in elementary education - Calvert, Heather (Kansas State University, 2018)
The model for professional learning communities began in the business sector as professional learning organizations. While there have been many different structures referred to as professional learning communities, the model referenced in this study was created by Rick DuFour, Rebecca DuFour, and Robert Eaker. In their model, collaborative teams work together to answer four guiding questions: What do we want students to learn? How will we know when they have learned it? What will we do for students who already know it? What will we do for students who did not learn it? The DuFour model has been noted in research to be one of the most powerful and impactful educational reform efforts. This study examines the role of the implementation process on the overall effectiveness of the professional learning community. The purpose of this interview study was to explore the experiences of five certified teachers. This qualitative study was informed by purposeful sampling intersected with criterion-based sampling. Participants selected needed to be a certified teacher who taught at the chosen site during the implementation process. Symbolic interpretivism grounded this study to elicit experiences during the professional learning community implementation that impacted the participant’s professional responsibilities. Findings of this study indicated that the implementation process was not the determining influence on how teachers and teacher leaders navigated their professional responsibilities and, in turn, the overall success of the professional learning community implementation. Instead, success was tied to the dispositions of each teacher and the anatomy of interactions based on those dispositions. Four specific personality dispositions were found in this study: Leading with Heart, Leading with Brain, Leading with Courage, and Leading with Leadership. The combinations of these dispositions effected how each participant navigated their professional responsibilities as well as their reciprocal relationships with their colleagues. This study raised implications about how combinations of different personality dispositions can be used to create teams of educators who will naturally accomplish the tasks of a professional learning community instead of being in conflict and tension with each other. Another implication was the notion that creating effective teams of teachers and teacher leaders could be based on personality dispositions and their consequent interactions versus the knowledge of one’s pedagogy. Lastly, this study raised implications regarding the ways in which professional learning communities could be better implemented in schools nationwide by creating more awareness amongst educational leaders and policy makers about building harmonizing professional learning communities.
Keywords: Professional Learning Communities; Educational Leadership; Arts-Based Inquiry; Elementary Education